Qualidade física e fisiológica de sementes de feijão submetidas à dessecação com diferentes princípios ativos e épocas de aplicação - Zocche, Eduarda (2022)
The common bean (Phaseolus vulgaris L.) is a legume of wide importance in both agriculture and cooking, worldwide. Its cultivation is greatly influenced by several factors, related to both cultural practices and environmental factors. The use of seeds of high physical and physiological quality, seeks to minimize such effects and increase final productivity. The choice of herbicide and the time for desiccation of the bean helps in obtaining them, due to the standardization in the maturation of the crop. Therefore, the objective of this study was to evaluate the influence of desiccants on the physical and physiological quality of bean seeds submitted to desiccation at different times and active principles. The experiment was conducted in the 2019/2020 harvest, on a rural property located in the municipality of Pato Branco/PR. The experimental design used was randomized blocks, with three replications and treatments arranged in a 4x4 factorial scheme, involving four application times (50%, 60%, 70% and 80% of the pods at the point of maturation), three desiccant herbicides (Glufosinato de amônio, Saflufenacil and Diquat) and witnesses. The cultivar used was IPR Tuiuiú. It is a cultivar of the black group with type II indeterminate growth habit and upright posture. The variables analyzed after harvest were weight of a thousand seeds, humidity, germination and accelerated aging. For the cultivar IPR Tuiuiú, none of the active principles used in the preharvest desiccation affected the physiological quality of the seeds, when evaluated separately, as well as the different times in which they were applied. The application of Diquat with 60% of maturation of the plants, promoted the harvest with 16% of humidity. The highest germination percentages were achieved with the use of Diquat (99.17%) and Ammonium glufosinate (99.00%), both in the fourth desiccation season. The highest yield was 3916.22 kg/ha with 70% of maturation in the control, however it did not differ statistically from the other percentages of maturation and 70% of maturation with the use of Diquat.